Surgical management of Dupuytren contracture of the ring finger: a case report - Nugraha, Gede Ketut Alit Satria; Karna, Made Bramantya; Andika, Gde Dedy; Sunaria, Made (International Journal of Research in Medical Sciences, 2020)
Dupuytren’s disease, also called Dupuytren’s contracture or palmar fibromatosis, is a condition in which the connective tissue under the skin of the palm contracts and toughens over time. The gold standard treatment for Dupuytren’s contracture is surgery. We present a case of Dupuytren’s contracture treated with Bruner incision which resulted in good functional outcome. A 79 year old male presented to our Orthopaedic Clinic RSUP Sanglah Denpasar with the complaints of pain and stiffness on his left ring finger since 5 years ago. Patient had same history with his right hand and had operation 20 years ago. The patient underwent release of contracture using Bruner incision and had no complaint in 6 month follow-up. Extension deficit was <5°, reduction of contracture was >50%, the Patient and Observer Scar Assessment Scale (POSAS) gave overall opinion of the scar being minimal. The Dupuytren's disease etiology remains uncertain, with genetics perceived as most probable factor. Despite short-term success, there is a high rate of recurrent contracture with additional comorbidities such as wound-healing complications and neurovascular injury. In this case, the patient was treated using fasciotomy with Bruner incision and had satisfying outcome. Fasciotomy is known to have less complication in terms of recurrence. Dupuytren disease is characterized by abnormal thickening of the palmar fascia beneath the skin and the gold standard of treatment is surgery. This case presented surgical treatment using Bruner incision which had satisfying outcome in 6 month follow-up.